Gut microbiota and gastrointestinal tumors: insights from a bibliometric analysis - Chen, Chaofan; Wang, Xiaolan; Han, Xu; Peng, Lifan; Zhang, Zhiyun (Frontiers in Microbiology, 2025)
IntroductionDespite the growing number of studies on the role of gut microbiota in treating gastrointestinal tumors, the overall research trends in this field remain inadequately characterized.MethodsA bibliometric analysis was conducted using publications retrieved from the Web of Science Core Collection (up to September 30, 2024). Analytical tools including VOSviewer, CiteSpace, and an online bibliometric platform were employed to evaluate trends and hotspots.ResultsAnalysis of 1,421 publications revealed significant geographical disparities in research output, with China and the United States leading contributions. Institutionally, the University of Adelaide, Zhejiang University, and Shanghai Jiao Tong University were prominent contributors. Authorship analysis identified Hannah R. Wardill as the most prolific author, while the International Journal of Molecular Sciences emerged as a leading journal. Rapidly growing frontiers include “proliferation,” “inhibition,” “immunotherapy,” “drug delivery,” and “tumorigenesis.”DiscussionThis study provides a comprehensive overview of research trends and highlights emerging directions, aiming to advance scientific and clinical applications of gut microbiota in gastrointestinal tumor therapy.